Assessment of Changes in the Structure of the Labor Market under the Influence of the Corona Crisis in Kazakhstan - A. А. Alshanskaya; T. А. Azatbek (Экономика: стратегия и практика)
The state of the labor sphere depends on many factors: the introduction of new technologies, demographic trends, the aggravation of international competition, the strengthening of the influence of globalization, but the coronavirus pandemic has had the greatest impact in recent years. The study aims to analyze the patterns of labor market development in Kazakhstan in the context of the coronavirus pandemic and assess its impact on the state and structure of the market. To achieve the goal, the methods of analysis and synthesis within the framework of a structural and functional approach were used in the work. This article presents the characteristics of the Kazakhstan labor market in the period before and after the introduction of quarantine restrictions. The positive and negative consequences of the pandemic and its impact on the labor market have been identified, including an increase in unemployment, a decrease in employment, gender and sectoral transformation of the labor market and a slowdown in external and internal labor migration flows. The industries most and least affected by the pandemic are highlighted. In particular, the sector of so-called “contact” services suffered the most, which, as a rule, is characterized by high labor intensity, relatively low wages, as well as an increased share of informal employment and self-employment. It is emphasized that the most important direction in the transformation of the domestic labor market will be its flexibility. The results obtained in the course of the study allow us to formulate proposals for improving the state policy of development and regulation of the labor market.